DAMPAK PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CORPORATE IMAGE: STUDI KASUS PT NEWMONT NUSA TENGGARA KABUPATEN SUMBAWA BARAT - Lidiawati (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2020)
This research is aimed at (first) determining the effect of the implementation of CSR programs in education, health, environment, economy, socio-culture on the corporate image, (second) determining which variable is mostly dominant to affect the corporate image. This research is associative research aiming at determining the correlation between two or variables. The populations of this research are all community members in West Sumbawa, while samples were selected through purposive sampling. The data were collected through questionnaires distributed to respondents, and then were analyzed using multiple linear regressions. The analysis using multiple linear regressions of research showed that CSR program in education did not have significant and positive effect on the corporate image. CSR in health did not have significant and positive effect of the corporate image. CSR in environment had significant and positive effect of the corporate image. CSR in economy had significant and positive effect of the corporate image. CSR in sociio-culture did not have significant and negative effect of the corporate image. The CSR in economy is most dominant in affecting the corporate image